What does advanced practice mean to Australian paediatric pharmacists? A focus group study. (16th April 2014) - Stacey, Sonya R.; Coombes, Ian; Wainwright, Claire; Cardiff, Lynda; Whitfield, Karen
Abstract Objectives The aim of this study was to explore perceptions and attitudes of Australian paediatric pharmacists about advanced pharmacy practice and to identify suitable methods of assessment for this level of practice. Methods Four focus groups (with 31 participants) were held in 2012 with Australian hospital pharmacists who work with children. Written notes and audio recordings were used to produce verbatim transcriptions and extract themes. Key findings There was consensus across groups that formal recognition of advanced pharmacy practice was valuable to the profession and to individuals. Elements should include a strong grounding in clinical practice, commitment to education, research and service improvement outside the department and institution. A framework for career development should be used to describe the levels of practice leading to advanced practice. Assessment should involve multiple separate criteria, and incorporate direct observation, peer review and a professional portfolio. Postgraduate qualifications are desirable but not considered essential. Different knowledge and skills are required in paediatrics; however, the definition of advanced practice remains the same. Conclusions Recognition of advanced practice is valuable for the profession and for individuals. Multiple methods of assessment should be used. Specialty areas such as paediatrics can be defined and assessed similar to other specialties, with acknowledgement of the specific paediatric knowledge and skills required.